Pemberdayaan Teman Sebaya Dalam Meningkatkan Pengetahuan Gizi Remaja Kelebihan Berat Badan - Retno Wahyuningsih (Jurnal Gizi Prima (Prime Nutrition Journal), 2020)
Background : Being overweight in adolescents needs to be addressed early so as not to become a health problem in the future. Adolescents who are obese can be treated with peer education. Methods : Quasi-experimental, randomized pre-post control group on 39 high school students aged 14-18 years were divided into two groups: 1) a treatment group with peer nutrition counseling, 2 control groups with classical counseling. Results : Research that differentiates the knowledge before and after peer counseling (treatment group) with a significance of 0.000 (p <0.05), and the control group (classical counseling) with a significance of 0.001 (p <0.05). Conclusion : Peer counseling can increase knowledge.